2017
DOI: 10.5152/turkjorthod.2017.17032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone and Prophylactic Antimicrobial Applications on Shear Bond Strength of Orthodontic Brackets

Abstract: Objective: The present study aimed to evaluate the effects of ozone and prophylactic antimicrobial applications on the shear bond strengths and bond failure interfaces of orthodontic brackets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Activated charcoal, an abrasive agent, can be included in the formula of a dentifrice to encourage whitening [13]. Additional bleaching agents, like hydrogen peroxide, alter the dentin and enamel's natural colour in a more profound and long-lasting manner [14]. Although the peroxide concentration in these products is lower than the concentration used in trays (home use) or office bleaching techniques, data confirming their oxidant action have already been published, as shown by Hohlen et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…Activated charcoal, an abrasive agent, can be included in the formula of a dentifrice to encourage whitening [13]. Additional bleaching agents, like hydrogen peroxide, alter the dentin and enamel's natural colour in a more profound and long-lasting manner [14]. Although the peroxide concentration in these products is lower than the concentration used in trays (home use) or office bleaching techniques, data confirming their oxidant action have already been published, as shown by Hohlen et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…Also there are some emerging products gaining popularity such as use of ozone in the form of gas, water, or gels. [15] Chlorhexidine gluconate is a cationic biguanide with broad-spectrum antimicrobial action, whose effectiveness in decreasing the formation of dental biofilm (plaque) and gingivitis have been demonstrated in several clinical studies. It is considered as the positive control (gold standard), to which all other anti-plaque agents should be compared.…”
Section: Discussionmentioning
confidence: 99%
“…The application of ozone to enamel is an effective method of disinfection in several situations, such as before fissure sealant use or orthodontic bracket adhesion. 29,30 Ozone neutralizes bacteria and organic components on fissure and enamel surfaces because of its high activity and oxidation properties. It has therefore been suggested that some physical properties of enamel and the retention of restorative materials may affect ozone application.…”
Section: Discussionmentioning
confidence: 99%